Ok, now that you have changed it again ....
but still have the denominator as ambiguous.
I will read it as
( (2x^-4y^-1)(2y^4z^-1) )^-2/(2yx^3z^0)
(4x^-4 y^3 z^-1)^-2 /(2y x^3)
= (1/16)(x^8 y^-6 z^2)/(2y x^3)
= (1/32)(x^5 y^-7 z^2
or
= x^5 z^2/(32y^7)
Let me try again, because I keep getting something different.
This is the problem:
( (2x^-4y-1)(2y^4z^-1) )^-2/2yx^3z^0
Can you please help me simply this. I didn't get what you got.
Thanks.
4 answers
(2x^-4y^-1) = 2/(x^4 y)
(2y^4z^-1) = 2y^4/z
so, the numerator is
(2/(x^4 y) * 2y^4/z)^-2
= (4y^3 / x^4 z)^-2
= (x^8 z^2)/(16y^6)
Put all that over (2x^3 y) and you have
(x^5 z^2) / (32y^7)
(2y^4z^-1) = 2y^4/z
so, the numerator is
(2/(x^4 y) * 2y^4/z)^-2
= (4y^3 / x^4 z)^-2
= (x^8 z^2)/(16y^6)
Put all that over (2x^3 y) and you have
(x^5 z^2) / (32y^7)
We agree, Reiny, so it must be right!
nice, bob posted this question 3 times and each time there was a change in the way he typed it.